Dinâmica da secreção de néctar em Zeyheria montana Mart. (Bignoniaceae) relacionada à atividade dos beija-fores polinizadores - Dias Netto, Catarina Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The Cerrado is home to important biodiversity areas in the state of Sao Paulo. Therefore, research on the reproduction of species of this biome are essential to help conservation programs. Pollination is the main mechanism by which outcrossing plants perpetuate their populations, and the attractive, such as nectar, are of vital importance to many anthophilous animals and essential to the maintenance of interactions with pollinators. In this context, the objective of this study was to investigate the ecological dynamics of secretion and sugar composition of floral nectar in Zeyheria montana, an ornithophilous exclusive Cerrado species, visited preferentially by Colibri serrirostris, also exclusive to this biome. This dynamic was assessed in isolated flowers in pre-anthesis, using microsyringes to collect nectar and manual refractometer to measure the concentration. Experiments were carried out to evaluate production throughout anthesis, including the assessment of total daily production, the effect of successive removal, the rate of production during the day and night and changes in concentration and composition of sugars, which was performed in HPLC (High Performance Liquid Chromatography). The rate of nectar production was about three times greater at night with a concentration two times lower, resulting in a supply of large amounts of dilute nectar in the early morning hours, peak of visitation for hummingbirds. Moreover, the production of nectar was more pronounced before the anthesis, and is available to visitors already in newly opened flowers, which are preferentially visited by C. serrirostris. There was an increase in the nectar production of flowers in the group with successive manual removal upon the control group, suggesting that the withdrawal by visitors stimulates the production, ensuring the availability of the resource including flowers previously visited... (Complete abstract click electronic access below)

O Cerrado abriga áreas de importante biodiversidade no estado de São Paulo. Por isso, pesquisas sobre a reprodução de espécies desse bioma são fundamentais para subsidiar programas de conservação. A polinização é o principal mecanismo através do qual as espécies alógamas perpetuam suas populações, sendo os atrativos, tais como néctar, de importância vital para diversos animais antófilos e essenciais à manutenção das interações com os polinizadores. Neste contexto, o objetivo deste estudo foi investigar aspectos ecológicos da dinâmica de secreção e da composição de açúcares do néctar floral em Zeyheria montana, uma espécie ornitófila exclusiva do Cerrado, visitada preferencialmente por Colibri serrirostris, também exclusiva desse bioma. Essa dinâmica foi avaliada em flores isoladas em pré-antese, uitlizando-se microseringas para coleta do néctar e refratômetro manual para medir a concentração. Foram realizados experimentos de avaliação da produção durante toda a antese, incluindo a avaliação da produção total diária, o efeito da remoção sucessiva, a taxa de produção durante o dia e a noite e a variação na concentração e composição de açúcares, a qual foi realizada em CLAE (Cromatografia Líquida de Alta Eficiência). A taxa de produção de néctar foi cerca de três vezes maior no período noturno com concentração duas vezes menor, resultando em uma oferta de grande quantidade de néctar diluído no início da manhã, horário de pico de visitação dos beijaflores. Além disto, a produção de néctar foi mais expressiva anteriormente à antese, estando disponível para os visitantes já em flores recém abertas, as quais são preferencialmente visitadas por C. serrirostris. Observou-se um incremento na produção de néctar no grupo de flores com remoção manual sucessiva em relação ao grupo controle, sugerindo... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Biodiversidade; Cerrado